Pelatihan dan Pengembangan Sumber Daya Manusia pada UMKM Melalui Keterampilan Digital dalam Produksi Pangan - Adiguna, Patria; Sutariyono, Sutariyono; Aisha, Neila; Herawati, Tuti; Nurrahman, Syafran; Saefullah, Aep; AR, Rasmawati; Hakim, Melati Puspita; Syaputra, Riawan; Sitohang, Ronny Marthin (Journal of Community Research & Engagement, 2024)
This training aims to address human resource management (HRM) in the digital era and efforts to enhance the productivity of small and medium enterprises (SMEs). The challenges faced by SMEs, such as low productivity, added value, and product quality, are also a primary focus of this training. The activity was conducted on Saturday, May 25, 2024, at Jl Benda Permai III, Kampung Parakan Rt 06 Rw 09 Pondok Benda, Pamulang District, South Tangerang. The implementation methods included seminars, discussions, and hands-on practice. The participants consisted of 10 lecturers from STIE Ganesha and 20 business owners of Dimsum and cricket farmers. The training results indicated that HR professionals need to master strategic competencies, including understanding organizational values, talent management, leadership, and the use of digital technology. Additionally, they need to position the business strategically, build trust-based relationships, and manage various business pressures. The training also emphasized the importance of modernizing business systems and systematic policies as an alternative to increasing regional competitiveness and improving SME performance. Digital skills development, financial management, and information technology proficiency were identified as crucial needs for SME actors. This training provided valuable insights for HR professionals and SME stakeholders in understanding the importance of HRM in the digital era and enhancing SME productivity. Implementing effective strategies in HRM and productivity improvement will help achieve sustainable SME development goals and make a more significant contribution to the national economy